2004
DOI: 10.1111/j.1600-0528.2004.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standardized method for comparing fluoride ingested from toothpaste by 1.5‐3.5‐year‐old children in seven European countries. Part 2: Ingestion results

Abstract: The amount of fluoride ingested that is likely to be a risk factor for the development of dental fluorosis during tooth formation is equivocal and was found to vary widely between European countries. There appears to be a need for clearer health messages regarding the use of fluoridated toothpaste by young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
4
38
0
4
Order By: Relevance
“…There is a high correlation between the child's age, fl uoride concentration in toothpaste and the risk of developing dental fl uorosis [Cochran et al, 2004]. This has led to recommendations to minimize excessive fl uoride ingestion after toothbrushing, by using a small amount of toothpaste or by using a product with low fl uoride concentration.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high correlation between the child's age, fl uoride concentration in toothpaste and the risk of developing dental fl uorosis [Cochran et al, 2004]. This has led to recommendations to minimize excessive fl uoride ingestion after toothbrushing, by using a small amount of toothpaste or by using a product with low fl uoride concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, fluoride ingestion through swallowing toothpaste plays a decisive part. Children aged 1.5-2.5 swallow an average of 64.3-83.9% of the fluoride in toothpaste [Cochran et al, 2004b]. Bottenberg et al [2004] showed that brushing twice or more per day significantly increases the risk of developing fluorosis.…”
Section: Discussionmentioning
confidence: 99%
“…Children from Iowa were 0-36 months old, while children from the present study were from the same age (19-38 months). Studies evaluating only the dose obtained from the use of fluoridated dentifrice reported that 9.9% of European children [Arnadottir et al, 2004;Cochran et al, 2004d] and 19.5% of Brazilian children [Oliveira et al, 2007] are exposed to the dose limit of 0.05-0.07 mg F/kg body weight. The European study was conducted in seven countries, only one of which had a fluoridated water supply.…”
Section: Discussionmentioning
confidence: 99%